Technological Pedagogical Content Knowledge Analysis - Wati Susilawati; Hamdan Sugilar (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2021)
The ability to understand content and pedagogical knowledge are two non-negotiable things that must be mastered by teachers. In today's digital era, teachers are required to understand and be adaptive to the use of technology, so that knowledge of content, pedagogy, and technology becomes an important point of teacher knowledge today. This study purposes to analyze the ability of students' technology pedagogic content knowledge of prospective mathematics teachers by using qualitative descriptive methods. The research subjects are prospective students of mathematics teachers at universities in Bandung Indonesia who are researching the final project of scientific work in junior high school. The research instruments were questionnaires, observations and interview formats. The data analysis activity include: data collection, reduction, presentation and verification. The document analysis includes the learning process, lesson plans, implementation of learning, The use of information technology-based learning media, evaluation of learning, reflection of the learning process, results of questionnaires and interviews. The findings show that students’ ability to have knowledge of technology pedagogical content for prospective mathematics teachers is good category. Students are already skilled at deciphering big ideas. Prospective teachers have been able to develop learning implementation plans and carry out learning in accordance with the 2013 curriculum companion guidelines. Overall, understanding of the pedagogical content knowledge of teachers' technology needs to be improved when utilizing integrated and effective learning technology, so that teachers are more adaptive to the technology used appropriately and effectively wise.